1991
DOI: 10.1002/eji.1830210437
|View full text |Cite
|
Sign up to set email alerts
|

Surface expression by mononuclear phagocytes of an epitope shared with mycobacterial heat shock protein 60

Abstract: Bone marrow-derived macrophages were stained with a variety of monoclonal antibodies (mAb) with specificity for the mycobacterial heat shock protein (hsp) 60 or with specific rabbit antiserum raised against mycobacterial hsp 60. The mAb ML30 as well as the specific antiserum brightly stained bone marrow-derived macrophages whereas all the other mAb as well as normal rabbit antiserum gave no or negligible reactivity. Surface expression of the shared epitope is observed by day 3 of in vitro cultivation and marke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
25
0

Year Published

1992
1992
2007
2007

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(25 citation statements)
references
References 21 publications
(13 reference statements)
0
25
0
Order By: Relevance
“…The data represent means Ϯ SD of three to four experiments performed in quadruplicate. Significant differences to C3H/HeN (and C57BL/6) macrophages are indicated as ‫,ءءء‬ p Ͻ 0.001. response to diverse types of stress (3,4). We therefore have proposed that autologous hsp60 may serve as danger Ag to the innate immune system (2).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The data represent means Ϯ SD of three to four experiments performed in quadruplicate. Significant differences to C3H/HeN (and C57BL/6) macrophages are indicated as ‫,ءءء‬ p Ͻ 0.001. response to diverse types of stress (3,4). We therefore have proposed that autologous hsp60 may serve as danger Ag to the innate immune system (2).…”
Section: Discussionmentioning
confidence: 99%
“…R ecent studies have suggested that autologous heat shock protein 60 (hsp60) 3 serves as a danger signal to the innate immune system. Mouse or human macrophages, as well as endothelial or smooth muscle cells, were found to elicit a proinflammatory response when incubated with recombinant human hsp60 (1,2).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It is known, that HSP60, or at least parts of it, may be exposed on the cell surface [4][5][6]. Consequently, the next steps are to confirm the presence of this epitope within early atherosclerotic lesions and whether immune reactions against this epitope are involved in pathogenesis of atherosclerosis.…”
Section: Discussionmentioning
confidence: 99%
“…Since microbial HSP60s serve as major antigens in protection from, and pathogenesis of infectious diseases, autoimmune disorders such as rheumatoid arthritis, systemic sclerosis, psoriasis, Kawasaki's disease or Behcet's disease, are thought to be triggered by shared B-and T-cell epitopes cross-reactive between eukaryotic and prokaryotic HSP60 [3]. Interestingly, HSP60, which is physiologically active inside mitochondria, was found also on the surface of stressed eukaryotic cells, where it may serve as a danger signal and as target-(auto)-antigen for immune reaction [4][5][6].…”
Section: Introductionmentioning
confidence: 99%